If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 7 = 5x + 22 Reorder the terms: 7 + 10x = 5x + 22 Reorder the terms: 7 + 10x = 22 + 5x Solving 7 + 10x = 22 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 7 + 10x + -5x = 22 + 5x + -5x Combine like terms: 10x + -5x = 5x 7 + 5x = 22 + 5x + -5x Combine like terms: 5x + -5x = 0 7 + 5x = 22 + 0 7 + 5x = 22 Add '-7' to each side of the equation. 7 + -7 + 5x = 22 + -7 Combine like terms: 7 + -7 = 0 0 + 5x = 22 + -7 5x = 22 + -7 Combine like terms: 22 + -7 = 15 5x = 15 Divide each side by '5'. x = 3 Simplifying x = 3
| (x-4)+5(x-3)=2(3x-5) | | 2x+6=42 | | 7y-9=3(y+5) | | 6(7-8x)=186 | | (2x+3)(5x-1)=0 | | 5(t-2)=t+10 | | 9p+6=3(p+8) | | 4b=6b+-19 | | 4(x+2)=3x+11 | | 3x^2+10+8=0 | | 3p^2-28=27p | | 4(n-1)=n+14 | | 4y^3-3=-12y^2+y | | 10+2z=20 | | -6+x=-10 | | 12t-1=14t-5 | | 8k+10=13k-5 | | 3v^2-7v-20= | | 3a=5a-18 | | 6(x+2)=3(x-5) | | 5x+37=14x-62 | | x^2+5x+18=9 | | 4x+7=x+16 | | 15r+22=97 | | 3(x-4)+5(x+3)=2(3x-5)-6 | | 6(2x-5)=42 | | -4x+2(4-3x)=8-10x | | 9x-21=3+3 | | 3r+12=r+34 | | 4p+8=10p+2 | | -x^2+50x-350=0 | | 8t^2-6t=9 |